Investigating ecological factors involved in the incidence and severity of Puccinia punctiformis infection in Cirsium arvense - Astete Farfan, Almendra, author; Norton, Andrew P., advisor; Stewart, Jane E., advisor; Davis, Thomas Seth, committee member (Colorado State University. Libraries, 2024)
The rust fungus Puccinia punctiformis has been proposed as a biocontrol agent against the widespread and noxious weed Cirsium arvense due to its specificity and ability to systemically infect and eventually kill C. arvense. However, the incidence of P. punctiformis is low in naturally infected systems. The environmental conditions of temperature and humidity to which P. punctiformis teliospores are exposed after production and until germination could affect their viability, and consequently, compromise the occurrence of infections. The first chapter of this thesis investigated teliospore viability for germination after exposure to different relative humidity (5 %, 22 %, 62 %, 90 % RH) and temperature levels (-20 °C, 6 °C, 23 °C) over the course of a year. Results showed that teliospore germinability decreases significantly faster when exposed to 23 °C and 62 % RH, or 90 % RH, followed by -20 °C and 5 % RH, compared to all other conditions. Teliospore priming is a stimulation process prior to germination that has been associated with increased germination in some rust fungi (Morin et al., 1992; Bruckart & Eskandari, 2002; Fisher et al., 2009). The second chapter examined how priming P. punctiformis teliospores, either in water or in a 250 µl/L solution of the germination stimulator dodecyl-NCS dissolved in water, influences their germinability, as well as the incidence and severity of systemic infection in C. arvense plants inoculated with the primed teliospores. Results showed that priming teliospores in water, without a germination stimulator, results in significantly higher germination rates compared to priming them in the 250 µl/L dodecyl-NCS solution. Furthermore, both priming treatments enable significantly greater germination proportions compared to not priming the teliospores. Statistically, the incidence and severity of the systemic infections caused by water-primed teliospores were not significantly different from those caused by teliospores primed in the 250 µl/L dodecyl-NCS solution. Ultimately, our findings suggest that environmental factors such as warm-humid and cold-dry conditions, reduce teliospore germinability. Consequently, these conditions can also limit P. punctiformis infection in C. arvense. For biocontrol purposes, we recommend to collect and store teliospores avoiding these adverse conditions to maximize their viability. Furthermore, we propose using water-primed teliospores for P. punctiformis inoculations on C. arvense, as they exhibited increased germination rates and may facilitate systemic infections in both axillar and new shoots.
Zip file contains two supplementary photographs.
Keywords: rust fungi; teliospore germination; weed biocontrol; systemic infection; noxious weed; teliospore priming